Low intensity UV driven dual functional Cu-doped BiVO4 for enhanced methylene blue degradation and Staphylococcus aureus inactivation - Lih, Thien Kuang; Zheng, Alvin Lim Teik; Tan, Hui Yan; Sarbini, Shahrul Razid; Seng, Kelly Wong Kai; Chung, Eric Lim Teik; Andou, Yoshito; Tan, Kar Ban (Nature Research, 2025)
This study reported on a dual-functional Cu-doped BiVO4 photocatalyst synthesized via the hydrothermal method. Optimized 1 wt% Cu doping narrowed the bandgap to 2.24 eV, enabling 85% methylene blue (MB) degradation under low-intensity UV (13 W) within 180 min; a 5.1-fold enhancement over bare BiVO4. Radical trapping confirmed hydroxyl radicals (·OH) and superoxide radicals (·O2−) as the dominant reactive species. The catalyst retained > 92% efficiency over three cycles and exhibited moderate antibacterial activity against Staphylococcus aureus (12.6 ± 0.4 mm inhibition zone) in dark conditions, attributed to Cu2⁺ release. Cost analysis further revealed a competitive synthesis cost of approximately RM 7.57 per gram, supporting the economic viability for large-scale environmental remediation applications. The integration of dual photocatalytic and antibacterial functionalities, along with cost efficiency, reinforces the practical potential of Cu-doped BiVO4 in wastewater treatment applications.